Gripping controller design for a one-degree-of-freedom robotic hand model based on slip detection - Al-Shanoon, Abdulrahman Abdulkareem Sattoori (2016)
Robotic hands are considered mechatronic instruments that have the ability to perform activities beyond human capabilities. Robotic hands are widely used in manufacturing and dangerous nuclear industries as well as in precise applications, such as military or medical implementations. Repetitive and maintenance tasks are achieved with high accuracy when robotic hands are used. Consequently, the evolution of robotic hands is necessary to cover a wide range of tasks and by adding sensors, the grasping force can be measured and detected when the object slips. Measuring the grasping force between the robotic hand and an object can be achieved by using Force-Sensing Resistor (FSR), which have been widely used in robotics applications. Although this type of sensor has good features to handle diferent objects, the robotic hands that are currently using this sensor have never mentioned the object slipping feature during grasping operation. Slip sensing is signifcant in advance robotic manipulation. Therefore, this research has paid attention in the slipping detection process that occurs after gripping operation as well as the re-gripping of the object. The proposed work focuses on detecting the slip of the object and measuring the features of this slippage, such as distance and velocity. In this study, the robotic hand model employs an accelerometer sensor to detect the acceleration signal of the object during slippage. Furthermore, a common type of rotary encoder device is used to measure the distance of the slipping situation and velocity. A circuit is designed and implemented to collect the data of the sensors that would be analyzed. The robotic hand system comprises a new algorithm for data extraction and signal processing analysis that are measured from an object re-gripping operation based on slip detection information. The experimental works have concentrated on gripping an object with diferent weights (from 0.4118 N to 3.187 N) and detecting the slip situation to securely re-grip the object. The empirical findings have presented the output voltage of the FSR is directly proportional to the weight of the object, the minimum and maximum measured voltage are 0.209 V and 2.093 V respectively. In addition, the experimental results determine the subsequent re-gripping control mission based on slip events. The control system of an object re-gripping task is represented in Hooke's Law that estimates the required re-gripping force based on the distance of the object has slipped. The K values for accelerometer and rotary encoder are 0.0535+0.028 and 0.056+0.01 respectively. This conclude that the rotary encoder is better for slip detection in this robotic hand model